Citrus Polyphenol Hesperidin Stimulates Production of Nitric Oxide in Endothelial Cells while Improving Endothelial Function and Reducing Inflammatory Markers in Patients with Metabolic Syndrome - Rizza, Stefano; Muniyappa, Ranganath; Iantorno, Micaela; Kim, Jeong-a; Chen, Hui; Pullikotil, Philomena; Senese, Nicoletta; Tesauro, Manfredi; Lauro, Davide; Cardillo, Carmine; Quon, Michael J. (The journal of clinical endocrinology and metabolism, 2011)
Context:Hesperidin, a citrus flavonoid, and its metabolite hesperetin may have vascular actions relevant to their health benefits. Molecular and physiological mechanisms of hesperetin actions are unknown.Objective:We tested whether hesperetin stimulates production of nitric oxide (NO) from vascular endothelium and evaluated endothelial function in subjects with metabolic syndrome on oral hesperidin therapy.Design, Setting, and Interventions:Cellular mechanisms of action of hesperetin were evaluated in bovine aortic endothelial cells (BAEC) in primary culture. A randomized, placebo-controlled, double-blind, crossover trial examined whether oral hesperidin administration (500 mg once daily for 3 wk) improves endothelial function in individuals with metabolic syndrome (n = 24).Main Outcome Measure:We measured the difference in brachial artery flow-mediated dilation between placebo and hesperidin treatment periods.Results:Treatment of BAEC with hesperetin acutely stimulated phosphorylation of Src, Akt, AMP kinase, and endothelial NO synthase to produce NO; this required generation of H2O2. Increased adhesion of monocytes to BAEC and expression of vascular cell adhesion molecule-1 in response to TNF-α treatment was reduced by pretreatment with hesperetin. In the clinical study, when compared with placebo, hesperidin treatment increased flow-mediated dilation (10.26 ± 1.19 vs. 7.78 ± 0.76%; P = 0.02) and reduced concentrations of circulating inflammatory biomarkers (high-sensitivity C-reactive protein, serum amyloid A protein, soluble E-selectin).Conclusions:Novel mechanisms for hesperetin action in endothelial cells inform effects of oral hesperidin treatment to improve endothelial dysfunction and reduce circulating markers of inflammation in our exploratory clinical trial. Hesperetin has vasculoprotective actions that may explain beneficial cardiovascular effects of citrus consumption.